2022
DOI: 10.1111/hiv.13252
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐treatment and acquired antiretroviral drug resistance among people living with HIV in Tianjin, China

Abstract: ObjectivesThis study investigated the prevalence and patterns of pre‐treatment and acquired HIV drug resistance mutations among people living with HIV (PLWH) on antiretroviral therapy (ART) for 12 (±3) months in Tianjin, China.MethodsFrom Jan 2018 to Dec 2020, PLWH with HIV‐1 RNA greater than 1000 copies/mL visiting the ART clinic in the Tianjin Second People's Hospital were enrolled. Viral RNA isolated from blood samples were taken for genotypic resistance testing using an in‐house method. Major drug resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
4
7
1
Order By: Relevance
“…Additionally, we found a positive correlation between a high viral load and PDR, consistent with a European multicenter study [ 47 ], suggesting the importance of regular viral load monitoring. In contrast to some previous studies [ 32 ], gender (specifically the female gender) was not identified as a risk factor in our study. This could be attributed to the small number of women included in our study, which made it difficult to specifically assess the effect of gender on PDR.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Additionally, we found a positive correlation between a high viral load and PDR, consistent with a European multicenter study [ 47 ], suggesting the importance of regular viral load monitoring. In contrast to some previous studies [ 32 ], gender (specifically the female gender) was not identified as a risk factor in our study. This could be attributed to the small number of women included in our study, which made it difficult to specifically assess the effect of gender on PDR.…”
Section: Discussioncontrasting
confidence: 99%
“…The highest incidence of resistance was observed for NNRTI, with V179D and K65R being the predominant resistance mutations. These findings align with studies conducted in Tianjin [ 32 ] and Cameroon [ 33 ]. It has been widely reported that EFV and NVP, as first-line drugs, are frequently associated with the development of resistance [ 33 , 34 ].…”
Section: Resultssupporting
confidence: 92%
“…Results of the multivariable analysis indicated that individuals who had prior ARV drug exposure had 7.45 times greater odds of PDR compared to those without prior ARV drug exposure. Such findings are consistent with research from Mexico, African countries, and Northeast China [ 42 - 44 ]. There was an increasing trend of the proportion of CRF55_01B samples, rising from 2.3% in 2015 to 3.9% in 2018 and 4.1% in 2022 in China [ 34 ].…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have shown genotypes B and C are linked with an elevated likelihood of resistance. 9 , 10 Additional research is required to understand the discrepancies in the results. Further, the study’s sample size is relatively small to draw conclusions; hence, we need to reproduce the study in a larger population to corroborate these findings.…”
Section: Discussionmentioning
confidence: 99%